Denial and Deception : An Insider's View of the CIA - Mahle, Melissa Boyle (New York Nation Books, 2006)
Melissa Boyle Mahle is a counterterrorism expert who was the top-ranked female Arabist in the CIA when she retired as a covert officer in 2002. She received a letter of appreciation from the President for her work on the Middle East peace process. Since leaving the government, Ms. Mahle has worked as a private consultant on Middle Eastern political and security affairs. She lives in Virginia.
Include Bibliography and Index
Keywords: United States. -- Central Intelligence Agency. -- Intelligence service -- United States. -- Brainwashing -- United States